Insights into the roles of bacterial infection and antibiotics in Parkinson’s disease - Sheng, Shuo; Zhao, Shuo; Zhang, Feng (Frontiers in Cellular and Infection Microbiology, 2022)
Parkinson’s disease (PD) is one of the most common neurodegenerative disorders, which is accompanied with the classical motor symptoms and a range of non-motor symptoms. Bacterial infection affects the neuroinflammation associated with the pathology of PD and various antibiotics have also been confirmed to play an important role not only in bacterial infection, but also in the PD progression. This mini-review summarized the role of common bacterial infection in PD and introduced several antibiotics that had anti-PD effects.